Culture, board composition and corporate social reporting in the banking sector - Emma García-Meca; María-Victoria Uribe-Bohórquez; Beatriz Cuadrado-Ballesteros (Administrative Sciences, 2018)
This paper contributes to the debate on the corporate governance of financial institutions, by studying the effect of different board characteristics on the level of corporate social responsibility (CSR) disclosures of banks. For that, we use a sample composed by 159 banks over the period 2004-2010. We found that independent directors and gender diversity favor the disclosure CSR information in baking sector. But, these results are moderated by the national cultural system; concretely, previous positive effects of independence and diversity of banks' boards on CSR reporting are reduced in countries with a weaker cultural system, that is, individualist, masculine and vertically stratified societies, that are little indulgent and short-term oriented and show high levels of uncertainty avoidance.
Keywords: 350; corporate governance; board of directors; CSR disclosures; banking sector